Identifikasi Peptida BioaktIf dari Olahan Susu Fermentasi Tradisional Indonesia Sebagai Bahan Pangan FungsIonal Untuk Kesehatan - Soenarno, M. S.; Polli, B. N.; Febriantosa, A.; Hanifah, R. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2013)
Dangke and dadih is milk processing product from South Sulawesi and West Sumatera. Dangke had total plate count, yeast and mold, and lactic acid bacteria, respectively 6,4 x 108   cfu/g, 2,5 x 108 cfu/g, 2,8 x 105  cfu/g; and dadih had 7,3 x 108  cfu/mL, 9,0 x 107 cfu/mL, 1,5 x 105  cfu/mL. Dangke and dadih had higher sensitivity to Gram positive than Gram negative bacteria. Based on protein molecular weight, then dangke and dadih had peptide that included to glicoprotein.